Step by step: a motivational Instagram account / Muhammad Nabil Hazim Mohammed Nazri and Syazali Effendi A Wahab - Mohammed Nazri, Muhammad Nabil Hazim; A Wahab, Syazali Effendi (Academy of Language Studies, 2023)
Motivational content is more than simply helping people feel better about themselves; it is also about demonstrating how your brand, message, and goods/services can make them feel better about themselves. Quotes are brief, quick statements that can provide inspiration or stimulate meditation. In this project, the main focus is on the development of a Motivational Instagram account. The selection of motivational quotes to be part of social media is no stranger but must be strengthened in this day of age. Besides encouraging and motivating people, I hope that Step by Step will sustain the test of time as quotes will remain even in the future.